Compreendendo os sentimentos do adolescente em seu processo de iniciação sexual - Leticia Soares de Azevedo (2007)
This study came out from my interest in working with adolescents since my graduation in Nursing (Universidade Federal de Minas Gerais) during my practice as a nurse in Family Health Programs in Conselheiro Lafaiete City/MG and Belo Horizonte City/MG. The contact with youngsters in the communities and schools provoked several disquiets fromwhich the sexual aspects caught my attention. Thus, with the goal to understand the feelings involved in the process of sexual initiation, I went to meet them through this research, qualitative in character and phenomenologic in approach. I asked them the directional question: How do you feel about thinking in your sexual initiation? I addressed this question to twelve adolescents who have never experienced sex before.Six youngsters live in Belo Horizonte City, where I could be in touch with them through José Maria dos Mares Guia School, and six residents in Contagem City, who I invited to participate in the research through Health Center Unit, where I work as a nurse. The adolescents statements permitted me to unravel the phenomenon through the construction of four categories in two sub-categories: difficulty to talk about feelings;expecting the coming of the first sexual relation; think about the unknownexperience, arisen feelings; the influence of the family in the adolescentsbehaviour; thinking in the consequences after sex. To understand what the adolescents live, the analysis was based on phenomenologic philosophers and authors who deal with the sexuality in adolescence theme. The interviewed youngsters revealed fear, diffidence, anxiety, shame, worry and desire. In this context, professional support,active listen, precise orientations with empathy show our differential as nurses who deal with these feelings: the care in its deepest essence. It is necessary to improve the educational practices about sexuality and overcome the superficial biological patterns to reach an atmosphere where it is possible to promote conscious and reflective attitudes.Only in this way, we can achieve the project of a total sexual and reproductive health among youngsters.